Small‐molecule CFTR activators increase tear secretion and prevent experimental dry eye disease. Issue 5 (3rd February 2016) - Mores, Alyssa M.; Casey, Scott D.; Felix, Christian M.; Phuan, Puay W.; Verkman, A. S.; Levin, Marc H.
Abstract : Dry eye disorders, including Sjögren's syndrome, constitute a common problem in the aging population, with limited effective therapeutic options available. The cAMP‐activated Cl2 channel cystic fibrosis transmembrane conductance regulator (CFTR) is a major prosecretory channel at the ocular surface. We investigated whether compounds that target CFTR can correct the abnormal tear film in dry eye. Small‐molecule activators of human wild‐type CFTR identified by high‐throughput screening were evaluated in cell culture and in vivo assays, to select compounds that stimulate Cl – ‐driven fluid secretion across the ocular surface in mice. An aminophenyl‐1, 3, 5‐triazine, CFTRact ‐K089, fully activated CFTR in cell cultures with EC50 250 nM and produced an 8.5 mV hyperpolarization in ocular surface potential difference. When delivered topically, CFTRact ‐K089 doubled basal tear volume for 4 h and had no effect in CF mice. CFTRact ‐K089 showed sustained tear film bioavailability without detectable systemic absorption. In a mouse model of aqueous‐deficient dry eye produced by lacrimal ablation, topical administration of 0.1 nmol CFTRact ‐K089 3 times daily restored tear volume to basal levels, preventing corneal epithelial disruption when initiated at the time of surgery and reversing it when started after development of dry eye. Our results support the potential utility of CFTR‐targeted activators as a novel prosecretory treatment for dry eye.—Flores, A. M., Casey, S. D., Felix, C. M., Phuan, P. W., Verkman, A. S., Levin, M. H. Small‐molecule CFTR activators increase tear secretion and prevent experimental dry eye disease. FASEB J. 30, 1789–1797 (2016). www.fasebj.org